Case 3677: Proposed application of Article 1.3.7 to exclude as genus-group names the modifications of species-group names that are formed by addition of the standard suffix -ana or -iana. - Gittenberger, Edmund (Bulletin of Zoological Nomenclature)
(Acknowledgement of receipt published in BZN 72 (1): 2; Case not published). Following correspondence with the author, the Case is now closed.